NURSING AND AUDIOLOGY: : INTERDISCIPLINARY ACTION ACCORDING TO GERIATRIC DEMAND - Vinicius Lessa de Souza, Marcus (Health and Society, 2021)
Geriatrics help prevent and promote actions that help to minimize the impacts on the quality of life of the elderly. Being the nurse together with a multidisciplinary team, of vital importance in the development of these actions, The Nurse seeks to adapt the reality and the environment to which the elderly person is, thus enabling a better quality of life in this environment. The audiologist audiologist aims at a concern in hearing health, seeking to assist in the prevention and promotion of actions that help patients to have a more effective social interaction and avoid isolation in the face of difficulties that they may present. In short, the natural aging process causes damage to various functions of the human body, and one of them is auditory. The presence of hearing loss has several negative consequences for the quality of life of individuals, especially social isolation and in these cases hearing aids end up being strong allies to minimize the impacts that hearing loss causes on people's lives. Thus, this work aims to relate the issue of social isolation caused by hearing loss, increased risk of depression in the selection process and adaptation of hearing aids for the elderly and the role of the geriatric nurse aiming at improving the quality of life and preventing problems that may arise. In this study, a bibliographic search was made in the databases and an interface between two areas of health: Nursing and Speech Therapy, and its search to improve the quality of life of the elderly population as a social being.